Caerin 1.1/1.9-mediated antitumor immunity depends on IFNAR-Stat1 signalling of tumour infiltrating macrophage by autocrine IFNα and is enhanced by CD47 blockade - Junjie Li; Yuandong Luo; Quanlan Fu; Shuxian Tang; Pingping Zhang; Ian H. Frazer; Xiaosong Liu; Tianfang Wang; Guoying Ni (Scientific Reports)
Abstract Previously, we demonstrated that natural host-defence peptide caerin 1.1/caerin 1.9 (F1/F3) increases the efficacy of anti-PD-1 and therapeutic vaccine, in a HPV16 + TC-1 tumour model, but the anti-tumor mechanism of F1/F3 is still unclear. In this study, we explored the impact of F1/F3 on the tumor microenvironment in a transplanted B16 melanoma model, and further investigated the mechanism of action of F1/F3 using monoclonal antibodies to deplete relevant cells, gene knockout mice and flow cytometry. We show that F1/F3 is able to inhibit the growth of melanoma B16 tumour cells both in vitro and in vivo. Depletion of macrophages, blockade of IFNα receptor, and Stat1 inhibition each abolishes F1/F3-mediated antitumor responses. Subsequent analysis reveals that F1/F3 increases the tumour infiltration of inflammatory macrophages, upregulates the level of IFNα receptor, and promotes the secretion of IFNα by macrophages. Interestingly, F1/F3 upregulates CD47 level on tumour cells; and blocking CD47 increases F1/F3-mediated antitumor responses. Furthermore, F1/F3 intratumor injection, CD47 blockade, and therapeutic vaccination significantly increases the survival time of B16 tumour-bearing mice. These results indicate that F1/F3 may be effective to improve the efficacy of ICB and therapeutic vaccine-based immunotherapy for human epithelial cancers and warrants consideration for clinical trials.